Rate performance enhancement of lithium-ion battery using precise thickness-controllable-carbon-coated titanium dioxide nanowire array electrode via atomic layer deposition. (20th February 2020) - Choi, Taejin; Kim, Seong Dae; Yeo, Seungmin; Cheon, Taehoon; Kim, Soo-Hyun; Ahn, Jong-Hyun; Kim, Hyungjun
Abstract: An atomic layer deposition (ALD) of ultra-thin and conformal carbon shell is demonstrated as a powerful technique for enhancing the rate performance of a nanostructured Li-ion battery (LIB) electrode. Structuring conformal-carbon-shell-coated TiO2 nanowire (NW) arrays with precise thickness control can be realized via the ALD process using a CBr4 precursor and a hydrogen plasma reactant. The vertically-aligned TiO2 NWs grown via hydrothermal and annealing method are used as a complex nanostructure anode. Ultrathin carbon-shell-coated (thickness 1–2 nm) TiO2 NW anodes show long-term cyclability and excellent rate-performance (capacity retention of 96.5% after 500 charge/discharge cycles and 105 mAh g −1  at 30 C, 1 C = 230 mA g −1 ) whereas thick carbon-shell-coated (thickness 6–7 nm) TiO2 NW anodes exhibit lower rate capability than the bare TiO2 NW anode, which is attributed to fast charge and mass transport of conformal and ultrathin carbon shell. This carbon coating method by ALD can be potentially applied to various nano-sized electrodes with complicated structures with uniform and precise thickness control coating.